Effect of cavitation jet technology on instant solubility characteristics of soymilk flour: Based on the change of protein conformation in soymilk - Qi Gong; Caihua Liu; Yachao Tian; Yuxuan Zheng; Libin Wei; Tianfu Cheng; Zhongjiang Wang; Zengwang Guo; Linyi Zhou (Ultrasonics Sonochemistry, 2023)
The protein conformation of soymilk is the key to affecting the instant solubility of soymilk flour. This study aimed to evaluate the effect of cavitation jet treatment time (0, 2, 4, 6, and 8 min) on the instant solubility of soymilk flour based on the conformational changes of protein in soymilk. The results showed that the cavitation jet treatment for 0–4 min significantly unfolded the protein structure of soymilk and increased the content of soluble protein, which reduced the particle size and increased the electrostatic repulsion and the viscosity of soymilk. This was beneficial for soymilk droplets fully atomized and repolymerized in the spray drying tower, forming soymilk flour particles with large size, smooth surface, and uniform distribution. When the cavitation jet treatment time was 4 min, the wettability (from 127.3 ± 2.5 s to 84.7 ± 2.1 s), dispersibility (from 70.0 ± 2.0 s to 55.7 ± 2.1 s), and solubility (from 56.54% to 78.10%) of soymilk flour were significantly improved. However, when the time of the cavitation jet treatment was extended to 8 min, the protein of soymilk aggregated and the stability of soymilk decreased, which reduced the particle size and hurt the surface characteristics of soymilk flour after spray drying. It resulted in a decrease in the instant solubility of soymilk flour. Therefore, the cavitation jet treatment with proper time increases the instant solubility of soymilk flour by improving the protein conformation of soymilk.